Catalyst- and metal-free C(sp 2)–H bond selenylation of (N-hetero)-arenes using diselenides and trichloroisocyanuric acid at room temperature - José S. S. Neto; Isis J. A. Granja; Marcos R. Scheide; Marcelo S. Franco; Cassio A. O. Moraes; Adilson Beatriz; Dênis P. de Lima; Giancarlo V. Botteselle; Tiago E. A. Frizon; Sumbal Saba; Jamal Rafique; Antonio L. Braga (Scientific Reports, 2023)
Abstract In this paper, we report an eco-friendly approach for the C(sp 2)–H bond selenylation of imidazopyridines and other N-heteroarenes as well as simple arenes at ambient temperature. This new protocol consists of the reaction between (N-hetero)-arenes and the diorganyl-diselenides and trichloroisocyanuric acid (TCCA)-ethanol reagent system. In a short reaction time, the desired selenylated products were obtained regioselectively in good yields, with tolerance for a wide range of functional groups.